2019
DOI: 10.1037/ccp0000447
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of cognitive-behavioral therapy for alcohol or other drug use disorders: Treatment efficacy by contrast condition.

Abstract: Objective: This meta-analysis examined 30 randomized controlled trials (32 study sites; 35 study arms) that tested the efficacy of cognitive-behavioral therapy (CBT) for alcohol or other drug use disorders. The study aim was to provide estimates of efficacy against three levels of experimental contrast (i.e., minimal [k = 5]; nonspecific therapy [k = 11]; specific therapy [k = 19]) for consumption frequency and quantity outcomes at early (1 to 6 months [kes = 41]) and late (8+ months [kes = 26]) follow-up time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
135
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(142 citation statements)
references
References 78 publications
4
135
0
3
Order By: Relevance
“…8 For example, it is well known that cognitive behavioral therapy (CBT) is an effective treatment, but only a few studies have paid attention to patients' neuropsychological functioning; this approach could be inappropriate or insufficient for patients with cognitive impairments since it requires preserved cognitive capacities such as episodic and procedural memories and executive functions. 8,44,45 Furthermore, cognitive impairment can also influence readiness to change, active participation in group therapy, treatment compliance and outcomes. 9 Unfortunately, cognitive assessment is often missed in AUD treatment since neuropsychological test batteries are costly and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…8 For example, it is well known that cognitive behavioral therapy (CBT) is an effective treatment, but only a few studies have paid attention to patients' neuropsychological functioning; this approach could be inappropriate or insufficient for patients with cognitive impairments since it requires preserved cognitive capacities such as episodic and procedural memories and executive functions. 8,44,45 Furthermore, cognitive impairment can also influence readiness to change, active participation in group therapy, treatment compliance and outcomes. 9 Unfortunately, cognitive assessment is often missed in AUD treatment since neuropsychological test batteries are costly and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence supports the effectiveness of cognitive behavioural therapy (CBT) for treating SAD (Olatunji et al, 2010). CBT is also a widespread treatment for AUD, yielding moderate effects compared to no/minimal treatment, although a recent systematic review concluded it was no more effective than other established AUD therapies, such as motivational interviewing (Magill et al, 2019). Effective approaches for managing SAD or AUD cannot be assumed to generalise to individuals with comorbid anxiety and AUDs, who are typically excluded from treatment trials (Smith and Randall, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…CBT is one of the most commonly used psychotherapeutic interventions for the treatment of SUDs ( Substance Abuse and Mental Health Services Administration, 2014 ). CBT is a multisession intervention targeting cognitive, affective, behavioral and environmental risks in substance users that has shown its effectiveness in alcohol use reduction and other primary substances ( Magill et al., 2019 ). However, less is known about the effectiveness of CBT in amphetamine-type stimulant reduction.…”
Section: Effectiveness Of Digital Interventions For the Treatment Of mentioning
confidence: 99%
“…On the other hand, interventions containing multiple sessions often apply cognitive behavioral therapy (CBT), motivational interviewing (MI), community reinforcement approach (CRA), ecological momentary assessment (EMA), or a combination of several principles in “integrated therapeutic principles”, and are more commonly applied in more severe cases of substance use, including illicit substances. Several reviews and meta-analyses have indicated the effectiveness of different therapeutic principles in the reduction of substance use, including CBT (e.g., Magill et al., 2019 ), MI (e.g., DiClemente et al., 2017 ), CRA (e.g., Roozen et al., 2004 ), and EMA ( Clifford and Davis, 2012 ).…”
Section: Introductionmentioning
confidence: 99%